Dall'Isonzo. Diario di impressioni e sentimenti: traduzione, note e commento di Remo Castellini - Castellini, Remo (2021)
The first part of this book consists in the translation of Alojzij Res's diary from Slovenian into Italian language. The author of the diary reported from the Isonzo front of the First World War. The second part contains a critical part, which aims to analyse and present the work and the author more in detail.